Therapeutic advances of rituximab alone or plus other drugs for membranous nephropathy - Chao Zhang; Hui Liao; Rong-shan Li (Editorial Department of Journal of Clinical Nephrology, 2024)
Membranous nephropathy （MN） is a common pathological type of adult nephrotic syndrome. According to the etiology, MN is divided into idiopathic membranous nephropathy （IMN） and secondary membranous nephropathy （SMN）. IMN accounts for around 80% of MN patients. Glucocorticoid plus alkylating agents or calcineurin inhibitors （CNIs） are frequently prescribed. However, carcinogenic risk of alkylating agents and a high recurrence of disease after the dosing of CNIs have limited the applications of these two types of drugs. In the pathogenesis of MN, B cells play an important role of acting as antigen presenting cells. Rituximab （RTX）, a novel immunosuppressive agent, is a monoclonal antibody specific to B cell surface antigen CD20. In many recent clinical studies, RTX alone or plus other drugs has demonstrated a definite efficacy for MN. Whether or not patients benefit more from a single drug or a combination therapy is yet to be determined.